2023
DOI: 10.1002/jsfa.12936
|View full text |Cite
|
Sign up to set email alerts
|

Varietal impact on women's labour, workload and related drudgery in processing root, tuber and banana crops: focus on cassava in sub‐Saharan Africa

Alexandre Bouniol,
Hernan Ceballos,
Abolore Bello
et al.

Abstract: Roots, tubers and cooking bananas are bulky and highly perishable. In Africa, except for yams, their consumption is mainly after transport, peeling and cooking in the form of boiled pieces or dough, a few days after harvest. To stabilize, better preserve the products and, in the case of cassava, release toxic cyanogenic glucosides, a range of intermediate products have been developed, mainly for cassava, related to fermentation and drying after numerous processing operations. This review highlights, for the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 63 publications
(102 reference statements)
3
4
0
Order By: Relevance
“…In Benue state, Nigeria, there was no significant difference in the processing productivity and PPI of the tested genotypes but a significant difference was observed in the PPI of tested genotypes in Osun state, where TMS‐1 had a significantly higher PPI than the local and popular varieties and the breeders check, although no difference in the processing productivity of the individual operations was observed. Genotypes with high dry matter content have a higher gari yield in all locations, in line with Bouniol et al 32 …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In Benue state, Nigeria, there was no significant difference in the processing productivity and PPI of the tested genotypes but a significant difference was observed in the PPI of tested genotypes in Osun state, where TMS‐1 had a significantly higher PPI than the local and popular varieties and the breeders check, although no difference in the processing productivity of the individual operations was observed. Genotypes with high dry matter content have a higher gari yield in all locations, in line with Bouniol et al 32 …”
Section: Discussionsupporting
confidence: 88%
“…Our investigation demonstrated that differences between varieties contributed to the difference in processing productivity and thus to the possible drudgery experienced. This underscores the clear varietal differences in processing productivity observed by Bouniol et al 32 , who evaluated the processing productivity of processors and the loads carried from one processing step to the other on a larger and more contrasting set of cassava varieties in three locations across Nigeria and Benin (Bouniol et al 32 ). The observed genotypic influence on how champion processors evaluated the food product quality, also underscore that genotypes play a role in determining food product qualities.…”
Section: Discussionmentioning
confidence: 76%
“…8,23 In addition, easiness of peeling was reported for yam as one of the main purchasing criteria of fresh tubers, 24 and is also important in the case of cassava as it strongly impacts drudgery and productivity during processing. 25 A glassy sensory attribute evaluated in Colombia revealed additional information: glassiness was associated with moistness as perceived by sensory panellists, but at the same time with lower water absorption. This is likely because the water that was present in the samples after cooking was not fully absorbed by the starch fraction and instead remained on the surface and in the interstitial spaces, resulting in quicker release into the mouth upon biting, and hence a more moist perception.…”
Section: Discussionmentioning
confidence: 99%
“…43 The processing of gari-eba is a major sources of income for the many women who process and market these products. [43][44][45][46][47][48][49][50] Preparation of an evidence report: The process of reflecting on each step of the research and the resulting data, undertaken by the multidisciplinary team to create the evidence report, was important in highlighting linkages between characteristics/traits the stages of product transformation, and how they were valued by different food system actors. This provided learning for all team members (Box 3).…”
Section: Case Studiesmentioning
confidence: 99%
“…This analysis demonstrated the varietal effect on the productivity of the processors and thus the possible amount of labour involved. 50,51 These issues are reflected in the ranking of the characteristics in the evidence report.…”
Section: Case Studiesmentioning
confidence: 99%